Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10608-005-9637-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysphoria and Self-Esteem Following an Achievement Event: Predictive Validity of Goal Orientation and Personality Style Theories of Vulnerability

Abstract: B. M. Dykman (1998) proposed a goal orientation model of depression in which striving to prove self-worth in goal pursuits conferred depression vulnerability. This study replicated and extended the findings of B. M. Dykman (1998) by comparing goal orientation against 2 personality variables: autonomy and sociotropy. In a series of sessions around an achievement event, college students completed goal orientation, autonomy/sociotropy, and measures of dysphoria and self-esteem. For participants who were dissatisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
0
17
0
3
Order By: Relevance
“…situations, and there is a growing body of goal theory research examining interpersonal stressors. In addition, there is some research applying each theory to stressors in general or across situations (Dykman, 1998;Fortuna & Roisman, 2008;Lindsay & Scott, 2005;Mikulincer & Shaver, 2007a).…”
Section: Overview Of Similarities In the Theoriesmentioning
confidence: 99%
“…situations, and there is a growing body of goal theory research examining interpersonal stressors. In addition, there is some research applying each theory to stressors in general or across situations (Dykman, 1998;Fortuna & Roisman, 2008;Lindsay & Scott, 2005;Mikulincer & Shaver, 2007a).…”
Section: Overview Of Similarities In the Theoriesmentioning
confidence: 99%
“…Furthermore, from this perspective, it can be considered that the cognition and behavior of individuals are organized around the goals they pursue (e.g., Dweck, 1996;Dweck & Leggett, 1988;Dykman, 1998). Studies linking goals with depressive symptoms have demonstrated that goals drive and direct maladaptive (adaptive) cognitive and behavioral patterns in ways that promote (protect against) depressive symptoms (Dykman, 1998;Elliot & Dweck, 1988;Erdley, Cain, Loomis, Dumas-Hines, & Dweck, 1997;Kuroda & Sakurai, 2003;Lindsay & Scott, 2005;Sideridis, 2005). In light of these findings, the present study examined the onset of depressive symptoms during early adolescence by using a goal-orientation approach.…”
Section: Abstract Goals Stress Depression Peer Relationshipsmentioning
confidence: 99%
“…Furthermore, socially hypersensitive participants' self-worth was negatively correlated with the perceived impact of negative events, both social and nonsocial in nature, indicating their self-esteem was reactive to negative events in general. Conversely, Lindsay and Scott (2005) found that social hypersensitivity did not predict decreases in self-esteem in response to negative academic (nonsocial) feedback, suggesting socially hypersensitive individuals' self-esteem was reactive specifically to negative social feedback. These studies, however, used mixed combinations of social and nonsocial events, both major and minor, further highlighting the need for a study that assesses the impact of typical daily positive and negative, social and nonsocial events within a single sample.…”
Section: Adaptive Social Sensitivity Versus Social Hypersensitivitymentioning
confidence: 82%